Gender Equality and Social Inclusion in Climate Services Expanded Content for Senegal Agricultural Extension Curriculum - Hansen, James; Huyer, Sophia; Moore, Maya; Mbow, Khalifa (2024)
Inequality is deeply built into the way societies, economies and governments are structured. These structural inequalities can make it challenging to provide climate services that are accessible and benefit everyone. Even though climate services have the potential to improve the lives of rural farmers, they risk reinforcing existing inequalities if service providers fail to understand and address the unique needs and constraints of women and other historically marginalized populations, as well as include them in the design of services. Recognizing these populations as distinct user groups, with specific needs and barriers when it comes to accessing and utilizing climate services, is crucial. This training manual presents expanded curriculum content on gender equality and social inclusion for AES providers, to supplement the existing Climate Risk Management for Agricultural Extension (CRMAE) Senegal curriculum.